Critical Digital Literacies in Education 4.0: Preparing Students for the Uncertainties of Post-Truth World - Sary Silvhiany (Jurnal Bahasa dan Sastra, 2019)
Abstract: Industrial revolution 4.0 has brought forth the new drivers of change which include extreme longevity, the rise of smart machine and systems, computational world, new media ecology, super struc- tured organization, and globally connected world. Two of the prominent changes that greatly affect literacy education are the new media ecology and the digitally connected world. This paper focuses on how literacy is redefined by the advancement of digital technologies and the challenges of facing mis- information in the post-truth era. Based on the review of research on students’ ability to evaluate online information and assess the credibility of the sources, I offer recommendations for applying critical dig- ital literacies in all levels of education. Keywords: online information, critical digital literacies, post-truth Abstrak: Revolusi industri 4.0 mendorong pencetus perubahan, yang meliputi tingkat harapan hidup yang lebih panjang, munculnya mesin dan sistem pintar, dunia berbasis data komputasi, ekologi media terbaru, organisasi berbasis struktur super, dan dunia yang terkoneksi secara global. Dua agen peruba- han utama yang sangat berpengaruh pada pendidikan literasi adalah ekologi media terbaru dan dunia yang terkoneksi digital. Artikel ini berfokus bagaimana konsep literasi diredefinisikan oleh kemajuan teknologi digital dantantangan menghadapi informasi yang tidak benar dalam era post-truth. Berdasar- kan tinjauan riset mengenai kemampuan siswa dalam mengevaluasi informasi daring, dan kemampuan siswa dalam menilai sumber informasi, penulis memberikan rekomendasi mengenai aplikasi pembela- jaran digital critical literacies di semua jenjang Pendidikan. Kata-kata Kunci: informasi online, critical digital literacies, post-truth